Pemikiran Mohammed Ayoob Mengenai Multidimensionalitas Politik Islam Modern di Negara Islam Hingga ke Negeri Muslim (Indonesia) - Mutholingah, Siti (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2019)
Politics is something that is urgent in Islamic studies both in Islamic countries and in Muslim countries like Indonesia. The aim of the study is to analyze the thoughts of Mohammed Ayoob who offer the concept of modern Islamic politics and be multidimensional in nature. This study is a literature study with the main source is a book by Mohammed Ayoob entitled